The Implementation of COBIT 4.1 and COBIT 5-Based IT Governance Audits in the Ministry of Finance of Indonesia - Nur Imroatun Sholihat (The Indonesian Journal of Accounting Research, 2018)
Abstract: Lately, organizations including the governmental ones started to realize the crucial role of IT for their organizations. For example, in the last 3 years, The Ministry of Finance (MoF) has spent Rp1.244 billion (USD 93,57 million) for IT investment itself. Weill (2004) stated that the benefit received from the IT investment is influenced by its governance. To ensure that IT is well-governed, IT governance audit is performed. In Indonesia, Inspectorate General of MoF is the first and only internal audit organization to carry out IT governance audit to date. IT governance audit in the Ministry of Finance has also implemented the globally accepted framework, COBIT. For those reasons, IT governance audit practice in the MoF could be the acceptable benchmark for another public sector organization about the aforesaid area of audit. This research aims to get the understanding about the implementation of IT governance audits in the Ministry of Finance (MoF) and compare them with Assessor Guide: Using COBIT 5. This study is important because meanwhile IT governance audit is important, to the best of author’s knowledge, research about IT governance audit practice in Indonesia’s public sector is very limited. To achieve the research’s purpose, this research will be served as a qualitative descriptive research. The result showed that MoF’s IT governance audit practice implemented Assessor Guide: Using COBIT 5 with some adjustments were done. Despite being in the early stage, the IT governance audit which combined COBIT 4.1 and COBIT 5 assessment approaches is fair performed. Abstrak: Dewasa ini, organisasi termasuk organisasi pemerintah mulai menyadari peran penting TI untuk organisasi mereka. Misalnya, dalam 3 tahun terakhir, Kementerian Keuangan (Kemenkeu) telah menghabiskan Rp1.244 miliar (USD 93,57 juta) untuk investasi TI. Weill (2004) menyatakan bahwa manfaat yang diterima dari investasi TI dipengaruhi oleh tata kelolanya. Untuk memastikan bahwa TI dikelola dengan baik, audit tata kelola TI dilakukan. Di Indonesia, Inspektorat Jenderal Kemenkeu adalah organisasi audit internal pertama dan satu-satunya yang melakukan audit tata kelola TI hingga saat ini. Audit tata kelola TI di Kemenkeu juga telah menerapkan framework yang diterima secara global, COBIT. Untuk alasan tersebut, praktik audit tata kelola TI di Kemenkeu dapat menjadi tolok ukur bagi organisasi sektor publik lainnya tentang bidang audit tersebut.. Penelitian ini bertujuan untuk mendapatkan pemahaman tentang pelaksanaan audit tata kelola TI di Kemenkeu dan membandingkannya dengan Assessor Guide: Using COBIT 5. Studi ini penting sebab meskipun audit tata kelola TI penting, sepanjang pengetahuan penulis, penelitian tentang praktik audit tata kelola TI di sektor publik Indonesia sangat terbatas. Untuk mencapai tujuan penelitian, penelitian ini akan disajikan sebagai penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa praktik audit tata kelola TI Kemenkeu telah menerapkan Assessor Guide: Using COBIT 5 dengan beberapa penyesuaian. Meskipun berada di tahap awal, audit tata kelola TI yang menggabungkan pendekatan assessment COBIT 4.1 dan COBIT 5 telah dilakukan secara cukup baik.